FORMATION OF THE PROFESSIONALLY-PEDAGOGICAL COMPETENCE IN PREPARATION OF FUTURE TEACHERS IN KAZAKHSTAN - Zhanguzhinova, Meruyert; Magauova, Akmaral; Kertayeva, Kaliyabanu; Yessimova, Dinara; Toktarbayev, Darkhan; Kassenov, Khanat (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
The given article is considering the problem of insufficient formulation of theoretical bases of the Formation of Professional competence of students – future teachers of Vocational training in Kazakhstan upon requirements of a new educational paradigm, this impedes the integration into the global educational space. The analysis of the theories of EU, USA and UIS scientists revealed the novelty of the research in the implementation of the main directions of international experience in accordance with the requirements of the new educational paradigm, oriented towards competencies, based on knowledge, skills and attitude. The aim of the study is to reveal the professionally-pedagogical competence for the preparation of future teachers according to the structure of using primary methods of overview-theoretical analysis, including analysis and synthesis. The study design is based on the modern requirements of higher education, based on competencies of educational paradigm. The key results of the study will determinate suggestions on the Formation of the professional competence of future teachers on the example of the specialty Vocational training. On results of theories’ analyse will be revealed the structure of the professionally-pedagogical competence. The question of the study is how to improve the preparation of future teachers in Higher Educational Institutions, which is depending on modern requirements of educational paradigm based on competencies.